Answer:
The best first step in solving the equation is to subtract 3 from both-sides of the equation.
Explanation:
To solve this equation, the following steps are to be followed
3 + 3/6x = 5
First step: subtract 3 from both-side of the equation.That is;
3-3 + 3/6x = 5 -3
The equation becomes;
3/6x = 2
The second step is to multiply both-side of the equation by 6x. That is;
×
= 2 × 6x
(At the left-hand side of the equation, 6x will cancel-out 6x leaving us with just 3).
Our equation becomes;
3 = 12 x
Divide both-side of the equation by 12 to get the value of x
=
![(12x)/(12)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ks6v72fliupyd6o97ncfgnkhpq1f979yzy.png)
(On the right-hand side of the equation 12 at the numerator will be cancel-out 12 at the denominator leaving us with just x while at the left-hand side of the equation 3 will be divided by 12)
= x
x =
![(1)/(4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/iiq2xsk4vi9pqjukqb60xxgyxukyno498i.png)
Therefore, the best first step in solving the equation is to subtract 3 from both-sides of the equation.